IMPLEMENTATION OF AN INTERACTIVE DIALOGUE TRAINING MODEL BASED ON CHATGPT TO IMPROVE SPEAKING SKILLS - Munisatul Fahmiyah; Ahmad Faroji; Ubaidillah (El-Tsaqafah : Jurnal Jurusan PBA, 2026)
This study explores the implementation of a ChatGPT-based interactive dialogue training model for Arabic-speaking learners (maharah al-kalām) at SMA Darul Amanah. This research employed a qualitative case study design involving eleventh-grade students. Data were collected through classroom observations, interviews, and oral speaking performance tasks. The findings reveal that students showed increased confidence, more active participation in dialogue, and improved vocabulary use during speaking practice. In addition, students experienced reduced anxiety when practicing speaking through ChatGPT-assisted dialogue. These results indicate that ChatGPT can serve as an effective supportive medium for fostering a more engaging and student-centered environment for Arabic-language learning